2022
DOI: 10.1177/15280837221137353
|View full text |Cite
|
Sign up to set email alerts
|

An efficient virtual modeling regard to the axial tensile and transverse compressive behaviors of the twisted yarns

Abstract: The mechanical properties of yarns have a decisive effect on the performance of fiber-reinforced composite materials. Predictive simulations of the mechanical response of yarns are, thus, necessary for damage evaluation and geometric reconstruction of textiles. This paper proposed a quasi-fiber scale virtual modeling method regard to the axial tensile and transverse compressive behaviors of the twisted yarns. A stochastic properties model of the yarn was established for characterizing the statistical distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…In most finite element modeling, the yarn of woven fabric reinforcement consists of long synthetic fibers that are twistless and highly parallel to the principal axis direction of the yarn. However, many scholars have found that the yarn twist angle has significant effects on the mechanical properties of the woven flax fabric reinforced composites [28,29]. Therefore, it is necessary to take account of the twist yarn properties in the impact modeling of woven flax fabric reinforced composites.…”
Section: Introductionmentioning
confidence: 99%
“…In most finite element modeling, the yarn of woven fabric reinforcement consists of long synthetic fibers that are twistless and highly parallel to the principal axis direction of the yarn. However, many scholars have found that the yarn twist angle has significant effects on the mechanical properties of the woven flax fabric reinforced composites [28,29]. Therefore, it is necessary to take account of the twist yarn properties in the impact modeling of woven flax fabric reinforced composites.…”
Section: Introductionmentioning
confidence: 99%